Effects and mechanism of action of Huang-Lian-Jie-Du-Tang in atopic dermatitis-like skin dysfunction in vivo and in vitro. (10th August 2019) - Fan, Hui-Jie; Zhao, Xiao-Shan; Tan, Zhang-Bin; Liu, Bin; Xu, Hong-Lin; Wu, Yu-Ting; Xie, Ling-Peng; Bi, Yi-Ming; Lai, Yi-Gui; Liang, Hong-Feng; Zhou, Ying-Chun
Abstract: Ethnopharmacological relevance: Atopic dermatitis (AD), a disorder prevalent during childhood and adulthood, seriously affects the patient's quality of life. Although Huang-Lian-Jie-Du-Tang (HLJDT) has shown anti-inflammatory effects in previous studies, its effects and mechanism of action underlying AD disorder are still largely unknown. Objective: This study explored the anti-inflammatory and immunomodulatory effects of HLJDT on the AD-like dermal disorder, induced in vitro by lipopolysaccharide (LPS)-triggered inflammation, and in vivo by 2, 4-dinitrochlorobenzene (DNCB). Materials and methods: In vivo HLJDT effects were investigated by determining the severity of dermatitis, which consisted of observing signs of skin lesions, visually and through haematoxylin and eosin (HE) staining, in mouse ears and dorsal skin, measuring serum levels of interleukin (IL)-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, interferon (IFN)-γ, the tumour necrosis factor (TNF)-α, and determining the splenic index, number of splenic CD4 + /CD8 + T-lymphocytes, as well as the phosphorylation levels of mitogen-activated protein kinases (including MAPKs-p38, ERK, and JNK), IκB-α, and nuclear factor kappa B (NF-κB) (p65) within dermal lesions. Morphological changes in LPS-induced inflammation were observed under a microscope, and ELISA and qPCR assays were used to measure IL-1α, IL-1β, IL-6, and TNF-α expression levels. The protein expression levels of P-ERK/ERK, P-p38/p38, P-JNK/JNK, P-IKβ-α, and P-p65 were measured through western blotting. Additionally, p65 expression was assessed by immunofluorescence, and LPS binding to RAW264.7 cell membrane was studied with laser confocal microscopy. Results: HLJDT could remarkably mitigate DNCB-induced AD-like lesion symptoms, alleviating inflammatory mediator infiltration in mouse ears and dorsal skin tissue, down-regulating serum expression levels of IL-1α, IL-1β, IL-2, IL-4, IL-5, IL-6, IFN-γ, and TNF-α, normalising the splenic CD4 + /CD8 + T-lymphocyte ratio, and inactivating MAPKs (including p38, ERK, and JNK), IκB-α, and NF-κB (p65) in dorsal skin. Furthermore, HLJDT inhibited LPS-induced differentiation of RAW264.7 cells, as evidenced by the decreased protein and mRNA expression of IL-1α, IL-1β, IL-6, and TNF-α. Additionally, it decreased ERK, p38, JNK, IKβ-α, and p65 phosphorylation levels in the MAPKs/NF-κB pathway, inhibited p65 nuclear translocation, and reduced LPS binding to the RAW264.7 cell membrane. Conclusions: HLJDT significantly improved AD-like symptoms via inhibition of the MAPKs/NF-κB pathway. Therefore, administration of HLJDT might be a potential treatment for AD in the clinical setting. Graphical abstract: Image 1